Penilaian Konsumen terhadap Minuman Kopi Populer pada Roost Restaurant di The Nest Hotel Nusa Dua - Kadek Resta Dewi; Ni Putu Ariesta Budiani; I Gusti Agung Febrianto (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2026)
The high consumption of coffee as part of people's lifestyle and the dominance of Americano and Cappuccino variants in sales at Roost Restaurant necessitate an analysis of consumer assessments of these two beverages. Therefore, this study aims to determine consumer assessments of the popular Americano and Cappuccino coffee beverages at Roost Restaurant at The Nest Hotel Nusa Dua. This study uses quantitative descriptive analysis techniques with data collection techniques through documentation and questionnaires distributed to 82 respondents. Consumer assessments are analyzed based on five indicators, namely taste, aroma, balance, presentation, and price. The results show that all indicators for both coffee beverages are in the high category, meaning that consumer assessments of Americano and Cappuccino are good in all aspects. The indicator with the highest rating for Americano and Cappuccino is presentation, while the indicator with the lowest rating for Americano and Cappuccino is taste. These findings indicate that although consumer ratings are generally good, improvements in taste, especially for Americano, are still needed to enhance consumers' positive perceptions of the products served.